GENETIC ENGINEERING OF TOMATO PLANTS: A NARRATIVE REVIEW OF THE UTILIZATION OFAGROBACTERIUM AND CRISPR-CAS9 - Anatasya Putri Gusasi; Titania Rahma Aureria Inaku; Saputri Afra A. Pakaya; Nur Fadilah Sahran; Sintia ABD Rahman; Natasya Aprilia Putri Supardi (JIMR : Journal Of International Multidisciplinary Research, 2025)
Global population growth increases the demand for nutritious food, while tomato (Solanum lycopersicum L.) productivity often declines due to biotic and abiotic stress. CRISPR/Cas9 technology offers a precision approach to improving the nutritional quality, disease resistance, and metabolic efficiency of tomatoes. This review analyzes research from 2015 to 2025 on gene editing related to vitamin C enhancement, leaf morphology modification, fruit ripening, and strengthening resistance to pathogens such as TYLCV and powdery mildew, with Agrobacterium-based transformation proven effective in producing stable changes. However, challenges such as off-target risks and limited access to technology remain obstacles. Overall, CRISPR/Cas9 has the potential to accelerate tomato variety improvement for global food security, but further research is needed to enhance the precision and sustainability of its development.